Design Speaks English: Crafting Messages from Sketches to Slogans - Acfira, Lukytta Gusti (Universitas Terbuka, 2025)
In today’s globalized creative industries, English proficiency is not merely a supportive skill but a core component of professional literacy, especially in advertising. However, English for Specific Purposes (ESP) instruction often fails to reflect the communicative realities of design students, leading to a disconnect between language learning and domain-specific needs. This study explores how advertising students at Politeknik Negeri Media Kreatif engage with English when crafting brand messages in visual campaigns. The aim is to identify the linguistic challenges they face and the pedagogical adjustments needed in ESP instruction. Employing a qualitative research design, this study involved 15 advertising students as participants. Data were collected through document analysis of student-produced advertising materials, semi-structured interviews, and classroom observations. Thematic analysis revealed five core findings: (1) English use was shaped more by intuitive creativity than formal instruction; (2) students showed resourcefulness in digital-assisted writing but struggled with genre-specific tone and idiomatic accuracy; (3) multimodal synergy between text and visuals was enhanced by linguistic confidence; (4) collaborative language support was seen as lacking; and (5) students called for more context-specific ESP learning experiences. The study contributes to ESP and design education by proposing a reimagined ESP curriculum that includes task-based, genre-driven, and collaborative approaches tailored to creative disciplines. Findings suggest that integrating language instruction with design practice enhances students' communicative competence and their ability to produce globally resonant advertising content. This research supports a shift from generalized English training toward a more embedded, practice-oriented ESP pedagogy in design education.